Structural Characteristics of Economic Growth in Bulgaria - Raleva, Stela (Research Papers, 2020)
The paper studies the structural characteristics of GDP and its dynamics in Bulgaria. It interprets the resulting perspectives for economic growth and measures the degree of structural convergence of the Bulgarian economy with the Eurozone. The empirical analysis leads to the conclusions that the level and the dynamics of GVA have been dominated by the services, and Bulgaria converges with the Eurozone most strongly in the industry and most weakly in the agriculture, forestry and fisheries, as the deviation in aggregate production structure does not tend to decline. Furthermore, in the income structure of GDP, the increase in the relative share of compensation of employees leads to convergence with the Eurozone, but has an adverse effect on investment and economic growth.
Keywords: GDP production structure; GDP income structure; Structural convergence; Eurozone; Economic growth